Delayed Neurological Deterioration after Depressed Fracture over Superior Sagittal Sinus: Our Experience with 13 Patients - Elshanawany, Ahmed; Ragab, Mahmoud (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2020)
Objective To present our experience in the diagnosis and management protocol of 13 patients with a depressed skull fracture over the superior sagittal sinus (SSS) who developed delayed neurologic deterioration.Patients and Methods This retrospective study was conducted in the Neurosurgical Department, Assiut University Hospitals, between May 2012 and May 2017. All patients with a depressed skull fracture over the SSS were reviewed. Only those patients who were neurologically intact after trauma but suffered delayed neurologic deterioration were included in this study. Preoperative characteristics of age, sex, cause of trauma, type and site of the depressed skull fracture, and clinical presentation were reviewed and evaluated. Neuroimaging including brain computed tomography and computed tomography venography were evaluated.Results Of 612 patients with depressed skull fractures admitted to our department, 63 had the fracture segment on the SSS. Thirteen patients, nine males and four females, met the inclusion criteria (age range: 5–42 years). The most common cause of trauma was assault from others (seven patients). Eight patients had a compound depressed fracture; the other five fractures were simple. Interval between trauma and neurologic deterioration ranged between 4 days and 3 weeks. Clinical deterioration included decrease of consciousness, headache, blurred vision, and repeated vomiting. Deterioration of consciousness was seen in four patients. Eight patients had sixth cranial nerve palsy. Visual deterioration was seen in four patients. All the included patients were operated on for elevation of the depressed segment. Eleven patients improved; two patients who presented initially with visual deterioration did not improve. Their visual deterioration persisted after surgery. For both these patients, lumbar puncture revealed high cerebrospinal fluid (CSF) pressure. Clinical improvement followed the insertion of a thecoperitoneal shunt.Conclusion Increased intracranial pressure (ICP) may follow a depressed fracture over the SSS. It may occur immediately after trauma or later. Surgical decompression with elevation of the depressed segment is indicated. Persistence of manifestations of raised ICP despite elevation of the depressed segment indicates the occurrence of an SSS thrombosis. CSF pressure should be measured to confirm the diagnosis and consider a thecoperitoneal shunt.
Keywords: depressed fracture over superior sagittal sinus; surgical elevation; manifestations of increased intracranial pressure; benign intracranial hypertension